Spatio-temporal evolution and coupling relationship between biodiversity and urbanization in the areas along the Yellow River of Shandong province - Yingjun Sun; Wenxue Meng; Fang Wang; Haifeng Han; Mingxin Sui; Zhen Jian (Scientific Reports)
Abstract Mastering the coupling relationship and driving mechanism between urbanization and biodiversity is of great significance to ecological protection and regional sustainable development. The study took areas along the Yellow River of Shandong province (AYRSP) as the study area, which have the most rich and unique biodiversity resources in the whole basin. First, this study constructed a new indicator system of biodiversity based on remote-sensing data from species, ecosystem, and landscape to monitor and evaluate the spatial heterogeneity. The result was quantified by the proportion of key biodiversity areas, based on Sustainable Development Goal 15.1.2 from The United Nations. Then, the urbanization system was evaluated based on panel data. At last, the coordination relationship, lead-lag type between biodiversity and urbanization, and key influencing factors of coupling system at the county scale in 2015–2021 were identified by combining multiple models. The results demonstrated that the biodiversity level was gradually declining, with a distribution pattern of “low in the western, and high in mid-southern and eastern regions.” The AYRSP still faced certain challenges in the sustainable development of biodiversity. The coupling coordination degree between biodiversity and urbanization showed an increasing trend with continuous improvement in the urbanization level. Only two counties were types of biodiversity-urbanization synchronous development. The results of grey relation degree model indicated that most of indicators were above 0.6 and the urbanization had a significant impact on the coupling system. This study established the evaluation system for biodiversity and urbanization at the small scale, which could provide theoretical reference for the sustainable development of county-level administrative region.